An Appraisal of the National Economic Empowerment and Development Strategy I (NEEDS I) in Nigeria: The Educational Perspective - Aderemi, Taiwo (Journal of Economics and Behavioral Studies, 2013)
This paper set out to assess the performance of the National Economic Empowerment and Development Strategy (NEEDS I) in Nigeria in relation to its educational goals. These goals include; increasing enrolment in primary and secondary schools, improving the quality of education, and increasing funding to this critical sector. Several economic reform programmes in Nigeria have been abandoned not because they had no accomplishments, but largely as a result of paucity of studies assessing them. No paper in the Nigerian literature has appraised the NEEDS I vis-Ã -vis its stated educational objectives. This paper therefore fills this void. In realizing the objective of this study, I adopted the before and after approach, which involves comparing educational performance indicators before the initiation of the NEEDSI and during the programme. The findings revealed improved performance of educational indicators such as female enrolment in primary schools, adult literacy rate, primary school completion rate, and Senior Secondary School Certificate Examinations during the NEEDS programme, although achievements were modest. Budgetary allocation to the sector as a proportion of total budget was below 10 per cent and less than the 25 per cent UNESCO recommendation. Funding to this sector should be increased and monitored in order to achieve sustainable improvements in educational outcomes. Completion rate in secondary school was also low. This paper therefore suggests the extension of the universal basic education scheme to the senior secondary level to reduce drop-out rates.